An adapted method for analyzing 4H silicon carbide metal-oxide-semiconductor field-effect transistors - Hauck, Martin; Lehmeyer, Johannes; Pobegen, Gregor; Weber, Heiko B.; Krieger, Michael (Communications Physics, 2019)
Silicon carbide (SiC) metal-oxide-semiconductor field-effect transistors (MOSFETs) are key devices for next-generation power electronics. However, accurate determination of device parameters from 3-terminal characteristics is hampered by the presence of interface traps. Here we present a method that, in contrast to previous evaluation schemes, explicitly considers those defects. A well-tractable parametrization of the SiC/SiO2-specific interface trap spectrum is introduced that reflects the body of known data. With this ingredient, we develop an analysis that targets for an accurate determination of device parameters from simple 3-terminal characteristics. For its validation, we investigate MOSFETs with significantly different defect densities. The resulting parameters – charge carrier density, mobility and threshold voltage – are in excellent agreement with Hall effect investigations on the very same devices, avoiding systematic errors inherent to conventional evaluation techniques. With this adapted scheme, 4H-SiC power MOSFETs, even packaged, can be meaningfully characterized, speeding up innovation cycles in energy-saving power electronics.<br
Keywords: silicon carbide; SiC; power electronic transistors; interface defects

Evaluation of 4H-SiC MOSFET transfer characteristics using machine-learning techniques - Lehmeyer, Johannes; Citak, Timon; Weber, Heiko B.; Krieger, Michael (Electronics Letters, 2023)

Intrinsic color centers in 4H-silicon carbide formed by heavy ion implantation and annealing - Kobayashi, Takuma; Rühl, Maximilian; Lehmeyer, Johannes; Zimmermann, Leonard; Krieger, Michael; Weber, Heiko B. (Journal of Physics D-Applied Physics, 2021)
We study the generation and transformation of intrinsic luminescent centers in 4H-polytype of silicon carbide via heavy ion implantation and subsequent annealing. Defects induced by the implantation of germanium (Ge) or tin (Sn) have been characterized by photoluminescence (PL) spectra recorded at cryogenic temperatures. We find three predominant but as-yet-unidentified PL signatures (labeled as DI1–3) at the wavelength of 1002.8 nm (DI1), 1004.7 nm (DI2), and 1006.1 nm (DI3) after high dose implantation (> 4 × 1013 cm-2) and high temperature annealing (> 1700°C). The fact that the DI lines co-occur and are energetically close together suggest that they originate from the same defect. Regardless of the implanted ion (Ge or Sn), a sharp increase in their PL intensity is observed when the implantation damage becomes high (vacancy concentration > 1022 cm-3), indicating that the lines stem from an intrinsic defect caused by the damage. By tracking the PL signals after stepwise annealing, we examine how the overall intrinsic defects behave in the temperature range of 500 – 1800○C; the silicon vacancies formed by the implantation transform into either divacancies or antisite-vacancy pairs with annealing at about 1000°C. These spectra signatures are strongly reduced at 1200°C where the so-called TS defects are maximized in luminescence. As a final stage, the DI defects, which are most likely formed of antisites and vacancies, emerge at 1700°C. Our results provide a knowledge on how to incorporate and manipulate the intrinsic luminescent centers in SiC with ion implantation and annealing, paving the way for fully integrated quantum technology employing SiC.<br

NOMAD CAMELS: Configurable Application for Measurements, Experiments and Laboratory Systems - Fuchs, Alexander; Lehmeyer, Johannes; Junkes, Heinz; Weber, Heiko B.; Krieger, Michael (Journal of Open Source Software, 2024)

NOMAD CAMELS - Configurable Application for Measurements, Experiments and Laboratory Systems - Lehmeyer, Johannes; Fuchs, Alexander; Krieger, Michael; Weber, Heiko B. (2021)

Optical and electrical studies on the TS defect in 4H-SiC - Lehmeyer, Johannes; Fuchs, Alexander; Li, Zhengming; Bornträger, Titus; Candolfi, Fabio; Schober, Maximilian; Fischer, Marcus; Hartmann, Martin; Neu, Elke; Bockstedte, Michel; Krieger, Michael; Weber, Heiko B. (Journal of Physics D-Applied Physics, 2024)
When annealing a 4H silicon carbide (SiC) crystal, a sequence of optically active defect centers occurs among which the TS center is a prominent example. Here, we present low-temperature photoluminescence analyses on the single defect level. They reveal that the three occurring spectral signatures TS1, TS2 and TS3 originate from one single defect. Their polarization dependences expose three different crystallographic orientations in the basal plane, which relate to the projections of the nearest neighbor directions. Accordingly, we find a three-fold level-splitting in ensemble studies, when applying mechanical strain. This dependency is quantitatively calibrated. A complementary electrical measurement, deep level transient spectroscopy, reveals a charge transition level of the TS defect at 0.6 eV above the valence band. For a future identification, this accurate characterization of its optical and electronic properties along with their response to mechanical strain is a mileston

Quantitative Investigation of Near Interface Traps in 4H-SiC MOSFETs via Drain Current Deep Level Transient Spectroscopy - Hauck, Martin; Weiße, Julietta; Lehmeyer, Johannes; Pobegen, Gregor; Weber, Heiko B.; Krieger, Michael (Materials Science Forum, 2016)
Keywords: MOSFET; drain current DLTS; Hall effect in MOS channel; interface traps; NITs; POA

Removing the orientational degeneracy of the TS defect in 4H-SiC by electric fields and strain - Rühl, Maximilian; Lehmeyer, Johannes; Nagy, Roland; Weißer, Matthias; Bockstedte, Michel; Krieger, Michael; Weber, Heiko B. (New Journal of Physics, 2021)

Strain-Dependent Photoluminescence Line Shifts of the TS Color Center in 4H-SiC - Lehmeyer, Johannes; Fuchs, Alexander; Bornträger, T.; Popp, Matthias Albert; Weber, Heiko B.; Krieger, Michael (Defect and Diffusion Forum, 2023)
We present a detailed study of the behavior of the photoluminescence (PL) of the TS color center in 4H-SiC under controlled mechanical strain. We have investigated the TS1 line under varying strain, including its reaction to compression and tension. We use emission polarization measurements to gain access to the orientation of the underlying defects. We put our results in context with previous findings and find good agreement, corroborating the proposed microscopic model.
CRIS-Team Scopus Importer:2023-11-03
Keywords: Color Center; Mechanical Strain; Photoluminescence; Photophysics

The Optical Properties of the Carbon Di-Vacancy-Antisite Complex in the Light of the TS Photoluminescence Center - Schober, M.; Jungwirth, N.; Kobayashi, Takuma; Lehmeyer, Johannes; Krieger, Michael; Weber, Heiko B.; Bockstedte, M. (Defect and Diffusion Forum, 2023)
The TS center is a promising temperature-stable photoluminescence center in 4H SiC. Here we investigate the carbon di-vacancy-antisite complex in the framework of ab initio theory as a tentative model for the TS center. We identify optical transitions of the basal complexes with the TS lines based on excitation energies, Stark shifts, and radiative characteristics. Charge-state-control of the TS center in p- and n-type Schottky contacts is demonstrated. Our experimental findings are consistent with the positively charged carbon di-vacancy-antisite complex.
CRIS-Team Scopus Importer:2023-09-01
Keywords: Ab Initio Theory; Charge-State Control; Color Center; Photoluminescence; Photophysics; Stark Effect